An ER assembly line of AMPA-receptors controls excitatory neurotransmission and its plasticity - Schwenk, Jochen; Sprengel, Rolf (Neuron, 2019)
Excitatory neurotransmission and its activity-dependent plasticity are largely determined by AMPA-receptors (AMPARs), ion channel complexes whose cell physiology is encoded by their interactome. Here, we delineate the assembly of AMPARs in the endoplasmic reticulum (ER) of native neurons as multi-state production line controlled by distinct interactome constituents: ABHD6 together with porcupine stabilizes pore-forming GluA monomers, and the intellectual-disability-related FRRS1l-CPT1c complexes promote GluA oligomerization and co-assembly of GluA tetramers with cornichon and transmembrane AMPA-regulatory proteins (TARP) to render receptor channels ready for ER exit. Disruption of the assembly line by FRRS1l deletion largely reduces AMPARs in the plasma membrane, impairs synapse formation, and abolishes activity-dependent synaptic plasticity, while FRRS1l overexpression has the opposite effect. As a consequence, FRSS1l knockout mice display severe deficits in learning tasks and behavior. Our results provide mechanistic insight into the stepwise biogenesis of AMPARs in native ER membranes and establish FRRS1l as a powerful regulator of synaptic signaling and plasticity.
Gesehen am 06.02.2020